The Practice Of Ambarāshram Yoga For Children’s Character Building - Sugata, Made; Sudarsana , Ketut (International Journal of Psychosocial Rehabilitation, 2020)
Character building is a crucial aspect of the quality of human resources. It is obvious that the children’s quality characters determine the nation’s future progress. As the first and foremost education, family has a main role in shaping the characters of children. The relationship between husband and wife, parents and children, as well as the relationship among siblings that create interactive and educative atmosphere determine a succesful character education in the family environment. A program at Ambarāshramis expected to enrich, preserve, and advance Balinese cultures and traditions that have been passed down through generations. Diksha suputraprogram will encourage children and adolescents to explore their full potential to reach their dreams, goals and aspirations according to their talents and interests. Dikshasuputrais one of the yoga programs at Ambarāshramspecifically given to children and adolescent to encourage them to give honour to their ancestors and parents, get along well with their relatives, be able to achieve their goals, and be helpful to the family and nation. This study will describe the processes and benefits of diksha suputrain theAmbarāshramyoga activities in shaping the characters of children